Dose ótima econômica de nitrogênio em cana-de-açúcar aplicada via fertirrigação por gotejamento - Esperancini, Maura Seiko Tsutsui [UNESP]; Do Afonso, Paulo Fernando Nascimento [UNESP]; De Gava, Glauber José Castro; E Villas Boas, Roberto Lyra [UNESP] (My University, 2015)
Fertilization is an important factor to increase yield of sugar cane, and Nitrogen is one of the nutrients which most limits crop yield. Sugar cane in Brazil has been fertilized with doses between 60 to 120 kg ha-1 N-urea in ratoons. When countries with similar productivity are compared, N doses have been generally higher than 120 kg ha-1, and in some cases, have reached 200 kg ha-1 N. Fertilization has a great impact on the composition of production costs of the sugar cane crop. In 2011, in the middle southern region of Brazil, the exchange ratio, i.e., the necessary amount to buy one ton fertilizer was an average of 19.2 ton sugar cane. With 78% Nitrogen consumed in agriculture, Brazil stands out among the world´s leading importers of the nutrient. The amount of economic returns from commercial cultivation of sugar cane is mainly based on three points: physical performance, production cost and price of sugar cane. Therefore, economic studies on nitrogen application have a direct effect on profitability of the sugar cane crop. The experiment based on nitrogen application to sugar cane ratoons using targeted irrigation by dripping was conducted at the Research and Development Unit (UPD) in Jaú city/SP, Paulista Technology Agency of Agribusiness (APTA), middle-west center. The second ratoon SP80-3280 cultivar was evaluated. The experiment under field conditions consisted of three N rates in the 2008/2009 harvest (70, 140, 210 kg N ha-1). For achieving R$ 6,092.56 ha-1 net revenue, the optimal economic productivity was 139.9 t ha-1 sugar cane, using 170.2 kg ha-1 urea-N applied by dripping fertigation.
Economically optimal dose of nitrogen in sugar cane applied by dripping fertigation
Keywords: Irrigation; Optimal economic productivity; Sugar cane